A sustainability assessment framework for Philippine solar energy projects for off-grid stand alone applications - Encinas, Catherine S.
A sustainability assessment framework has been developed to assist key project implementers involved in solar energy projects in the Philippines. Five key project components, namely, marker/financial/economic, technical, socio-cultural, environmental, as well as policies were identified to be critical in assessing new solar energy projects. Sustainability indicators have been identified to gauge the status of the project with respect to the different components. Correspondingly, action items were recommended to aid the user in improving the development of the solar energy project. Solar energy projects have been undertaken by different sectors to address the basic needs of electricity, water and decent livelihood; specifically to remote areas in the country. To achieve these goals, the project must be sustainable by providing the service in the community for at least 10 years. The system must be working, performing its function and servicing the beneficiaries. The sustainability assessment framework will aid the renewable energy industry of the country, specifically sectors that have plans of pursuing and developing solar energy projects for off grid stand alone applications.